Analisis Tingkat Kebangkrutan Dengan Menggunakan Model Altman Z-Score Pada Perusahaan Maskapai Penerbangan Yang Terdaftar Di Bursa Efek IndonesiaHety Budiyanty - Yuliana Yuliana; Hety Budiyanty; Nurman Nurman; Anwar Anwar; Andi Mustika Amin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the potential bankruptcy of airline companies listed on the Indonesia Stock Exchange using the Altman Z-Score model. This research uses descriptive quantitative methods. This study aims to determine the potential bankruptcy of airline companies listed on the Indonesia Stock Exchange using the Altman Z-Score model. This research uses descriptive quantitative methods. The sample in this study is the financial statements of 3 airline companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2022 period. The data collection technique used in this study used secondary data. The data analysis technique uses the modified Altman Z-Score method. The results of this study show that PT Garuda Indonesia Tbk is in bankruptcy condition in 2016-2021, and in 2022 the company is different in gray area conditions. PT Air Asia Indonesia Tbk for seven years, namely in 2016-2022, was in bankruptcy condition. PT Indonesia Transport & Infrastructure Tbk was in bankruptcy condition in 2016-2021, and in 2022 the company was in a gray area condition..